2018
DOI: 10.1111/sltb.12521
|View full text |Cite
|
Sign up to set email alerts
|

Non‐suicidal Self‐injury Differentiates Suicide Ideators and Attempters and Predicts Future Suicide Attempts in Patients with Eating Disorders

Abstract: Objective We aimed first to identificate psychopathological variables differentiating between suicide ideators, suicide attempters and patients without suicide ideation or attempts, and second to identificate better predictors of suicide attempts longitudinally. Method We compared suicide ideation, hopelessness, borderline symptoms, frequency, types, number of different non‐suicidal self‐injury (NSSI) methods, intrapersonal and interpersonal functionality of NSSI in a sample of 238 patients with Eating Disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…While suicide attempts were low in this study ( n = 39), prior studies of individuals with eating disorders have indicated elevated risk as compared to their undiagnosed peers (Udo, Bitley, & Grilo, 2019). Furthermore, given the role that suicidal ideation and nonsuicidal self‐injury play in later suicide attempts (Pérez, Ros, Folgado, & Marco, 2019; Ribeiro et al., 2016), the current findings may connote risk of escalating suicidal behavior later in life.…”
Section: Discussionmentioning
confidence: 80%
“…While suicide attempts were low in this study ( n = 39), prior studies of individuals with eating disorders have indicated elevated risk as compared to their undiagnosed peers (Udo, Bitley, & Grilo, 2019). Furthermore, given the role that suicidal ideation and nonsuicidal self‐injury play in later suicide attempts (Pérez, Ros, Folgado, & Marco, 2019; Ribeiro et al., 2016), the current findings may connote risk of escalating suicidal behavior later in life.…”
Section: Discussionmentioning
confidence: 80%
“…perhaps unsurprising given the prevalence of these illnesses in the general population. Of concern is the elevated suicide rate noted across the ED spectrum, the highest observed in AN [ 58 , 140 , 149 ]. For people with AN, suicide attempts were mostly associated with comorbid mood and anxiety disorders [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-suicidal self-injury (NSSI), broadly defined, is the intentional harm inflicted to one’s body without intent to die [ 148 ]. Recognising NSSI is often a precursor for suicidal ideation and behaviour [ 149 ], together with the already heightened mortality rate for EDs, several studies have examined the association between EDs and NSSI. Up to one-third of patients with EDs report NSSI at some stage in their lifetime, with over one quarter having engaged in NSSI within the previous year [ 63 ].…”
Section: Psychiatric Comorbiditiesmentioning
confidence: 99%
“…Regarding convergent validity, PB and TB showed positive, significant correlations with frequency of NSSI and hopelessness. These associations show that the two factors of the IPTS, the perception of being a burden and loneliness and the perception of not receiving any kind of reciprocal care, are related to other factors included in the theory (hopelessness), but also to other variables classically linked to suicide, such as NSSI [i.e., (56,57)] supporting the validity of the INQ-15 for assessing suicide-like constructs. Likewise, PB and TB showed negative associations with the protective factor meaning in life.…”
Section: Discussionmentioning
confidence: 73%